American Evangelicals and the Arab-Israeli Conflict. - Inbari, Motti; Bumin, Kirill M (Journal of Church & State)
The article focuses on American Evangelicals and the Arab-Israeli Conflict and Israel conquered vast territories from Egypt. It mentions United Nations has adopted Resolution 242 after the war and Israel signed the Oslo Accords with the Palestinian Liberation Organization (PLO). It also mentions Egypt and Syria launched a surprise attack on Israel and application of Israeli sovereignty to Judea, Samaria, the Golan Heights.